Right to Information and Role of Libraries and Information System in Nepal - KARKI, MADHUSUDAN (TULSSAA Journal, 2006)
This article elucidates the importance of information as a modern resource. It depicts libraries as cultural institutions and states the pious role played by libraries as collector and disseminators of useful information. It states the provision of right to Information enshrined in Nepal’s and other countries’ constitutions, in the UN Charter. Finally, it states the existing situation of legal protection and Government stance regarding the Right to Information. TULSSAA Vol.4(3) 2006 pp.19-22